A fluorescent covalent organic framework with a brick-wall topology for the detection of Cu2+ promoted by the associated mechanism. (June 2023) - Li, Shaoxin; Zhao, Bing; Kan, Wei; Song, Tianshu; Zheng, Wang; Qi, Xin; Wang, Liyan; Song, Bo
Abstract: Fluorescent covalent organic frameworks have initially drawn considerable attention as they show the excellent porous performances as well as highly selective fluorescent properties. However, the relationship between the porous structure and response mechanism is still an unmet challenge up to date. Herein, a Schiff-base two-dimensional covalent organic framework (2D COF) (PI-TPA COF ) with rarely brick-wall network was constructed by concentrating a tritopic T-shaped building block and a ditopic linear linker. Its brick-wall AB stacking structure was characterized in detailed by powder X-ray diffraction analysis, FT-IR, nitrogen adsorption−desorption measurements as well as theoretical simulations. PI-TPA COF exhibited the highly selective fluorescent performance for Cu 2+ (detection limit of 0.03  n mol L −1 ) in the mixture of acetonitrile/water ( v / v  = 7:3), which was mainly ascribed to the associated mechanisms of the absorption competition quenching (ACQ) caused by the porous structure of PI-TPA COF and the coordination interaction between PI-TPA COF and Cu 2+ . Furthermore, PI-TPA COF was successfully applied to the detection of Cu 2+ in the real environmental water, which provides a new platform for the application of COF materials in the field of environmental protection. Highlights: A covalent organic framework (PI-TPA COF ) was constructed with rarely brick-wall network. It exhibited selectively fluorescent sensing for Cu 2+ with the detection limit of 0.03  n mol L −1 . Sensing mechanism was ACQ associated with coordination interaction. PI-TPA COF was successfully applied to the detection of Cu 2+ in the real environmental water.